Reflections of Madison County a photographic journey - Heffron, Mark F. (London Mitchell Beazley, an imprint of Reed Consumer Books Limited, 1994)
A collection of photographs, combined with poetry and poetic impressions by such writers as Rainer Maria Rilke, Rachel Carson, John Muir, Samuel Taylor Coleridge, W.B. Yeats, Thornton Wilder, Pierre-Auguste Renoir, Jules Laforgue, Robert Lowell, Robert Penn Warren, and Aldo Leopold.
Keywords: Madison County (Iowa) -- Pictorial works; Madison County (Iowa) -- Description and travel